2022
DOI: 10.3390/children9101583
|View full text |Cite
|
Sign up to set email alerts
|

The Laparoscopic Cholecystectomy and Common Bile Duct Exploration: A Single-Step Treatment of Pediatric Cholelithiasis and Choledocholithiasis

Abstract: Background: In recent years, complicated biliary tract diseases are increasingly diagnosed in children. Laparoscopic exploration of the common bile duct (LCBDE) followed by laparoscopic cholecystectomy has gained popularity in children. The aim of this study was to investigate the outcomes of LCBDE in children and compare them with the treatment outcomes of previously used endoscopic retrograde cholangiopancreatography (ERCP). Methods: From January 2000 to January 2022, a total of 84 children (78.5% female) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…LCBDE is an alternative strategy with the advantage of providing definitive treatment with a single procedure, limiting anesthesia, and having the likelihood of overcoming functional distal obstructions (e.g., sphincter spasm and sludge) by glucagon administration, ductal flushing or dilation [ 5 ]. Recently, Pogorelić et al confirmed that LCBDE is safe and feasible in pediatric patients, avoiding papillotomy or fluoroscopy [ 6 ]. Therefore, the trend should be directed toward less ERCP in favor of LCBDE, provided LCBDE is performed in centers with dedicated teams and instrumentation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCBDE is an alternative strategy with the advantage of providing definitive treatment with a single procedure, limiting anesthesia, and having the likelihood of overcoming functional distal obstructions (e.g., sphincter spasm and sludge) by glucagon administration, ductal flushing or dilation [ 5 ]. Recently, Pogorelić et al confirmed that LCBDE is safe and feasible in pediatric patients, avoiding papillotomy or fluoroscopy [ 6 ]. Therefore, the trend should be directed toward less ERCP in favor of LCBDE, provided LCBDE is performed in centers with dedicated teams and instrumentation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In children, ERCP and laparoscopic exploration of the common bile duct (LCBDE) can be performed safely and effectively. Still, recent literature suggests that LCBDE should be a method of choice in pediatric patients [ 6 ]. Skilling in pediatric patients has been supported by collaborating with pediatric gastroenterologists, pediatric surgeons, adult gastroenterologists, anesthesiologists, and radiology staff.…”
Section: Introductionmentioning
confidence: 99%
“…In case of complicated GB disease (choledocholithiasis, common bile duct dilatation, gallstone pancreatitis), ERCP is indicated to drain the biliary tree or to remove stones after sphincterotomy [33]. Recently, the literature suggests performing LCBDE instead of ERCP to provide a definitive treatment in a single procedure and reduce complications associated with the endoscopic operative approach (ERCP complication risk is 5-10%) [34][35][36]. Although there are conflicting previous reports, the pediatric DUCT criteria (common bile duct dilation, US choledocholithiasis, and total bilirubin ≥1.8 mg/dL) seem to estimate the risk of choledochal involvement with high accuracy (>76%), specificity (>78%), and negative predicted values (>79%) [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting results suggest a lack of direct association between CCY and hepatobiliary system cancers [ 16 , 17 ]. Meanwhile, laparoscopic cholecystectomy and common bile duct exploration (LCBDE) was shown to resolve this problem in one step without destroying the structure of Ampulla of Vater in the management of choledocholithiasis compared with CCY after ERCP [ 18 ]. The current evidence for the correlation between increased cancer risks in the pancreatic and hepatobiliary system and CCY or endoscopic sphincterotomy (ES) [ 19 ] is not completely clear.…”
Section: Introductionmentioning
confidence: 99%